P021 Differential ACPA binding to nuclear antigens reveals a distinct subset of acetylation cross-reactive autoantibodies in rheumatoid arthritis. (March 2019) - Wigerblad, G; Lloyd, KA; Sahlström, P; Ossipova, E; Chemin, K; Steen, J; Titcombe, PJ; Zhou, D; Stålesen, R; Rönnelid, J; Mueller, DL; Kaplan, MJ; et al.
Abstract : Career situation of first and presenting author: Young investigator. Introduction: Anti-citrullinated protein autoantibodies (ACPA) in RA patients target a wide range of modified proteins and recent findings reveal that monoclonal ACPA are cross-reactive due to recognition of shared consensus citrulline-peptide motifs. Among physiological targets of ACPA, citrullination in neutrophil extracellular trap (NET) products, have been postulated to be important. Objectives: We sought to characterize the anti-nuclear and anti-neutrophil reactivities of different patient-derived monoclonal ACPA. Methods: The study included ten recombinant single B-cell derived RA monoclonal ACPA-IgG with CCP2 reactivity from different cell subsets and compartments (1, 2). They were screened for HEp-2 ANA reactivity, and binding to apoptotic cells or stimulated neutrophils. Binding was compared to CRISPR PAD4 KO cells and neutrophils from PAD2 and PAD4 KO mice. Immunoprecipitation and mass spectrometry were used to identify modified nuclear ACPA targets, and ELISA and Western blot for mAb binding to acetylated epitopes. Results: Four out of ten ACPA clones exhibited strong binding to apoptotic cells, nuclear binding to activated neutrophils, and reactivity to NETs. Three of these were ANA positive. Another NET-reactive ACPA instead displayed a cytoplasmic binding pattern. This cytoplasmic NET-binding was PAD4-dependent, whilst nuclear-mediated NET reactivity was PAD-independent. Using apoptotic cells, acetylated histones were confirmed to be the primary targets of the nuclear reactivity, which could be explained by consensus-motif driven ACPA cross-reactivity. Specifically targeted acetylated histone peptides were identified and the anti-modified protein autoantibody (AMPA) profiles of the ACPA were found to correlate with cell binding. Conclusions: When investigating monoclonal ACPA, our novel data reveal a distinct subset of ACPA with nuclear binding patterns and AMPA activity with acetylated histones (and not citrullinated proteins) in NETs and apoptotic cells. References: Titcombe PJ, Wigerblade G, Sippl N, Zhang N, Shmagel AK, et al. Pathogenic citrulline-multispecific B cell receptor clades in rheumatoid arthritis. Arthritis Rheumatol 2018. doi:10.1002/art.40590 Steen J, Forsström B, Sahlström P, Odowd V, Israelsson L, et al. Human plasma cell derived monoclonal antibodies to posttranslationally modified proteins recognize amino acid motifs rather than specific proteins. Arthritis Rheumatol 2018. doi:10.1002/art.40699 Disclosure of Interest: None declared.